Secondary teachers' understandings of dyslexia in England and Greece - Papalouka, Aikaterini (2011)
This is a comparative study about secondary teachers’ understandings of dyslexia in England and Greece. Specifically the study focused on English and Greek teachers’ professional training related to dyslexia, the influence of politics and cultural context, the history of dyslexia in England and Greece, the different definitions (meanings) of dyslexia and the legislation related to dyslexia. The main goals of the study were to find out how dyslexia is conceptualised in the Greek and English educational systems and the implications of these understandings for training and professional development in both countries. The sample consisted of ten teachers of secondary schools (five English and five Greek) who had experience of dyslexic students in their classrooms. An illuminative approach was used to compile and explore these two fields, teachers and dyslexia in England and Greece. Narrative analyses were undertaken culminating in individual portraits and an analysis of the role of the teacher in both countries, the influence of the educational system and the social and cultural habits and outcomes.